Argumentative Indicators in Discourse A Pragma-Dialectical Study - Eemeren, Frans H.; Houtlosser, Peter; Henkemans, A. Francisca Snoeck; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
Argumentative Indicators: A Pragma-Dialectical Study identifies and analyses English words and expressions that are crucial for an adequate reconstruction of argumentative discourse. It provides the analyst of argumentative discussions and texts with a systematic set of instruments for giving a well-founded analysis which results in an analytic overview of the elements that are relevant for the evaluation of the argumentation. In the book a systematic connection is made between linguistic insights into the characteristics of argumentative discourse and insights from argumentation theory into the resolution of differences of opinion by means of argumentation.
The Identification of Argumentative Indicators -- The Ideal Model of a Critical Discussion as a Theoretical Framework -- Indicators of Confrontation -- Indicators of the Distribution of the Burden of Proof -- Indicators of Starting Points for the Discussion -- Indicators of Argument Schemes -- Indicators of the Argumentation Structure -- Indicators of the Conclusion of a Discussion.
Keywords: HUMANITIES; LOGIC; LINGUISTICS -- PHILOSOPHY; APPLIED LINGUISTICS; LANGUAGE AND LANGUAGES; HUMANITIES / ARTS; INTERDISCIPLINARY STUDIES; APPLIED LINGUISTICS; LANGUAGE EDUCATION; PHILOSOPHY OF LANGUAGE; PHILOSOPHY; LOGIC